The Effect of Life Skills Training on Marital Satisfaction and Happiness of Married Students - Seyedeh Zahra Sadati; Bahram Mirzaian; Yarali Dousti (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Effective communication and the establishment of a good communication pattern between husband and wife have a prominent role in marital satisfaction and can play a crucial role in creating a sense of security and happiness for couples. The purpose of this study was to investigate the effect of training basic life skills on marital satisfaction and happiness in married students. Materials and Methods: The research method was semi experimental with pretest-posttest design with control group. The statistical population of this study included all the 180 female married students of Islamic Azad University, Qaemshahr branch, in the academic year of 2017-2018. Among them, 60 students (30 in the experimental group and 30 in the control group) were randomly assigned (voluntarily) to two groups of experimental and control groups. The intervention, training basic life skills, was performed for the experimental group and pre-test and post-test were performed for both groups. Date were collected vie Marital Satisfaction Scale and Happiness Questionnaire. Data were analyzed by one-way analysis of covariance with SPSS-22 software. Results: The mean (SD) age of the participants in the experimental group was 32.7 (6.8) and in the control group 33.6 (7). The mean (SD) marital satisfaction score was higher after training basic life skills compared with before the training: 155.9 (41.1) vs. 120.1 (47), P<0.001. The mean (SD) happiness score of married students was higher after training basic life skills compared with before the training: 49.8 (11.6) vs. 38.9 (13.9), P<0.001. No differences were observed in the mean (SD) of the pre-test and post-test score among the control group. Conclusion: Training basic life skills increased marital satisfaction and happiness among married female students.